2013
DOI: 10.1177/1933719113485295
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Neuroactive Steroid Concentrations After Preterm Delivery in the Guinea Pig

Abstract: Background: Preterm birth is a major cause of neurodevelopmental disorders. Allopregnanolone, a key metabolite of progesterone, has neuroprotective and developmental effects in the brain. The objectives of this study were to measure the neuroactive steroid concentrations following preterm delivery in a neonatal guinea pig model and assess the potential for postnatal progesterone replacement therapy to affect neuroactive steroid brain and plasma concentrations in preterm neonates. Methods: Preterm (62-63 days) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
79
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 35 publications
3
79
3
Order By: Relevance
“…Additionally, the results indicate that there are sex differences in the influences of prematurity on these parameters, with males seemingly more affected by early delivery. Furthermore, one of the most important findings was that the deficiencies in neurodevelopment of ex-preterm males seen previously in neonates remained until juvenility, whereas females were able to restore their initial reductions (25,26). Our previous studies in guinea pigs showed markers of mature oligodendrocytes were reduced in preterm compared to term gestational age fetuses, and were markedly affected by preterm delivery in the neonatal hippocampus and subcortical white matter in both sexes (25,26).…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Additionally, the results indicate that there are sex differences in the influences of prematurity on these parameters, with males seemingly more affected by early delivery. Furthermore, one of the most important findings was that the deficiencies in neurodevelopment of ex-preterm males seen previously in neonates remained until juvenility, whereas females were able to restore their initial reductions (25,26). Our previous studies in guinea pigs showed markers of mature oligodendrocytes were reduced in preterm compared to term gestational age fetuses, and were markedly affected by preterm delivery in the neonatal hippocampus and subcortical white matter in both sexes (25,26).…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, one of the most important findings was that the deficiencies in neurodevelopment of ex-preterm males seen previously in neonates remained until juvenility, whereas females were able to restore their initial reductions (25,26). Our previous studies in guinea pigs showed markers of mature oligodendrocytes were reduced in preterm compared to term gestational age fetuses, and were markedly affected by preterm delivery in the neonatal hippocampus and subcortical white matter in both sexes (25,26). The use of an ex-preterm juvenile model in the present study allowed us to ascertain whether oligodendrocyte expression remains affected until childhood, when many of the school-related disabilities become apparent clinically.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations